Neuropathobiology of COVID-19: The Role for Glia - Tremblay, Marie-Eve; Madore, Charlotte; Bordeleau, Maude; Tian, Li; Verkhratsky, Alexei (Frontiers in Cellular Neuroscience, 2020)
SARS-CoV-2, which causes the Coronavirus Disease 2019 (COVID-19) pandemic, has a strong brain neurotropism via binding to the receptor angiotensin-converting enzyme 2 expressed by neurones and glial cells, including astrocytes and microglia. Systemic infection which accompanies severe cases of COVID-19 also triggers substantial increase in circulating levels of chemokines and interleukins that compromise the blood-brain barrier, enter the brain parenchyma and affect its defensive systems, astrocytes and microglia. Brain areas devoid of a blood-brain barrier such as the circumventricular organs are particularly vulnerable to circulating inflammatory mediators. The performance of astrocytes and microglia, glial as well as immune cells required for brain health, is considered critical in defining the neurological damage and neurological outcome of COVID-19. In this review, we discuss the neurotropism of SARS-CoV-2, the implication of neuroinflammation, adaptive and innate immunity, autoimmunity, as well as astrocytic and microglial immune and homeostatic functions in the neurological and psychiatric aspects of COVID-19. The consequences of SARS-CoV-2 infection during ageing, in presence of systemic comorbidities, and for the exposed pregnant mother and foetus will also be specifically covered.